A combination of potential psychobiotics alleviates anxiety and depression behaviors induced by chronic unpredictable mild stress - Chen Meng; Siyuan Feng; Zikai Hao; Hong Liu (npj Biofilms and Microbiomes)
Abstract Strains of Roseburia inulinivorans, Bacteroides uniformis, and Eubacterium rectale have exhibited multi-pathway therapeutic efficacy against anxiety and depression-like behaviors in chronic unpredictable mild stress (CUMS) rats. However, the combined therapeutic effects of these strains remain to be elucidated. Behavioral tests showed that a mixture of these strains reduced anxiety and depression-like behaviors. 16S rRNA sequencing revealed that the mixtures decrease the relative abundance of potentially pathogenic bacteria within the gut microbiota. Furthermore, the mixture increased the levels of butyric, isobutyric, and isovaleric acids in the gut and decreased pro-inflammatory factors in serum. It also lowered diamine oxidase, histamine in brain tissue, increased DL-kynurenine, and reduced cortisol secretion by the hypothalamic pituitary adrenal axis. In summary, the mixture significantly alleviated anxiety and depression-like behaviors.